Growth of Si nanowires in porous carbon with enhanced cycling stability for Li-ion storage - Tan, Li Ping (2014)
Si nanowires are successfully grown in porous carbon by supercritical fluid-liquid-solid (SFLS) process, which show high specific capacities and charge–discharge cycling stability as anode materials for Li-ion storage. The enhancement capacity and cycling stability of the Si nanowires/porous carbon composite nanostructures is attributed to the porous carbon serving as a highly conductive framework and absorption of volume changes of Si nanowires during the lithiation/delithiation process. At optimized condition, the Si nanowires/porous carbon electrodes maintain reversible capacities of 1678 mAh g-1 for the 100th cycle at a current density of 420 mA g-1, which is much better as compared to that of pure Si nanowires.